The Effectiveness of Problem-Based Learning-Based E-SWS on Sound Wave Material to Improve Students' Critical Thinking Skills - Asyifa Hanesty Putri; Hidayati Hidayati; Yenni Darvina; Hayyu Yumna (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2025)
Critical thinking skills are essential in facing the challenges of the 21st century, especially in physics learning, which requires analysis and problem solving. However, many students still find it difficult to develop these skills, especially in sound wave material, which is abstract and difficult to visualize. This study aims to determine the effectiveness of using PBL-based E-SWS in improving students' critical thinking skills. The method used is quantitative with a posttest-only control group quasi-experimental design. The research subjects were two 11th grade physics classes at SMAS Adabiah Padang: the experimental class used PBL-based E-SWS and the control class used conventional SWS. The instrument consisted of essay questions based on five critical thinking indicators. The results showed that the average posttest score of the experimental class was 73.984, which was higher than that of the control class, which was 63.083. The t-test showed that the t-count value of 2.167 was greater than the t-table value of 2.0003, with a significance level of 5%. These results indicate a statistically significant difference. It can be concluded that PBL-based E-SWS is effective in improving students' critical thinking skills in sound wave material.